Pengaruh Peran Core Self-Evaluation Dan Empowering Leadership Terhadap Employee Creativity Melalui Knowladge Sharing: Studi Pada Karyawan UKM Batik Lasem Sekar Mulyo, Rembang - Dini Fahriati; Rauly Sijabat; Rita Meiriyanti (Lembaga Pengembangan Kinerja Dosen, 2024)
This research examines the employees of UKM Batik Lasem Sekar Mulyo, Rembang. This research aims to determine the influence of the role of core self-evaluation and empowering leadership on employee creativity through knowledge sharing. The research method in this research is a quantitative research method. The population in this study were all employees with a total of 95 employees who worked at UKM Batik Lasem Sekar Mulyo, Rembang, while the sample in this study was 95 respondents. Determining the sample size used a non-probability sampling technique because the population was relatively small, so the technique taken was saturated sampling (census). Data analysis in this research used the SmartPLS version 3 program. The data analysis technique used was the Structural Equation Modeling (SEM) equation model. The results of the analysis and discussion show that the quality perception variable influences Core Self-Evaluation and influences Employee Creativity, Empowering Leadership influences Employee Creativity, Core Self-Evaluation influences Knowledge Sharing, Empowering Leadership influences Knowledge Sharing, Knowledge sharing influences Employee Creativity, Core Self-Evaluation has an effect on Employee Creativity, partially mediated by Knowledge sharing, and Empowering Leadership has an effect on Employee Creativity in Employees of UKM Batik Lasem Sekar Mulyo, Rembang, which is partially mediated by Knowledge sharing.